(3GdeRGL dLGdjfhSs - (3LGdjfhSs ((3eMeO Hf CMeO Hf eMeO GdagQi s)
(3ChdgG (B:s
(3ef gPg GdCSeGA , GdHOf GdPi ZdH Ydi eRGLg GdQWhHI fSH Edjg s
(3BNQgG (B:s
(3ef cJGH GdeRGL , hHJeGegG ced GdcJGH HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GfXQg eY Gdbhi GdWHjYjI dLGdjfhSs
(3hGfXQ Qbe (B" 28" (3ef agQS GdWH HYfhGf cJGH GdCeRLIs
(3hgh GdcJGH GdSGOS ef LhGeY GdEScfOQGfjjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B230 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs